A theoretical and empirical investigation of property rights sharing in outsourced research, development, and engineering relationships. (29th March 2013) - Carson, Stephen J.; John, George
<x xml:space="preserve">Abstract</x> This article considers the use of property rights to structure ex post bargaining positions in client‐sponsored RD&E. By focusing on the positive externality created by uses of the technology not targeted by the client, the theory produces a novel set of predictions that diverge from standard transaction cost and property rights reasoning; that is, greater contractor property rights are associated with more transaction‐specific investments by the client. Contractor property rights are also predicted to increase as environmental uncertainty increases and as more applications of the technology fall outside the client's intended fields of use. Contract‐level data from 147 RD&E agreements in technology‐intensive settings provide support for these predictions. A secondary examination shows that clients who share property rights with their contractors face reduced opportunism during project execution. Copyright © 2013 John Wiley & Sons, Ltd.